2012
DOI: 10.7314/apjcp.2012.13.9.4733
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco-Related Chronic Illnesses: A Public Health Concern for Jamaica

Abstract: Background: Tobacco use is a leading cause of preventable morbidity and mortality from non-communicable diseases. The objectives of the study were to determine the percentage of annual income used to purchase tobacco-related products and treat tobacco-related illnesses, and assess the characteristics of smokers and their awareness of the health-related risks of smoking. Method: Stratified and snowball sampling methods were used to obtain information (via a 17-item, close-ended questionnaire) from 85 adult resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 35 publications
0
5
1
Order By: Relevance
“…Studies have traditionally reported better knowledge of risks with higher levels of education (Roychowdhury et al, 2005;Panda et al, 2012;Binnal et al, 2013). However the present study was in contrast to the study by Crawford et al, (2012) who reported no relation between awareness among smokers and their level of education.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Studies have traditionally reported better knowledge of risks with higher levels of education (Roychowdhury et al, 2005;Panda et al, 2012;Binnal et al, 2013). However the present study was in contrast to the study by Crawford et al, (2012) who reported no relation between awareness among smokers and their level of education.…”
Section: Discussioncontrasting
confidence: 56%
“…However, knowledge regarding impotence associated with smoking was low, similar to findings of the present study. There is also considerable evidence which shows that individuals involved in smoking do not necessarily have sufficient knowledge regarding ill effects of tobacco usage (Hu et al, 2006;Crawford et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Tobacco use is a major public health issue worldwide [ 6 ]. The tobacco-related carcinogen nitrosamine, 4-methylnitrosamino-1-3-pyridyl-1-butanone (NNK), is a major component and the most potent carcinogen in cigarette smoke [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although smoking, air pollution, exposure to carcinogens (such as asbestos), ionizing radiation etc., have been shown to be risk factors for lung cancer (Bhaskarapillai et al, 2012;Crawford et al, 2012;Zhang et al, 2012;Demirci et al, 2013;Babacan et al, 2014;Hajmanoochehri et al, 2014;Luqman et al, 2014), the pathogenic mechanism and the interactions between these risk factors are not entirely clear. Especially, the role of meteorological geographic factors in lung cancer is inconclusive.…”
Section: Introductionmentioning
confidence: 99%